Integrated metabolome and microbiome analysis reveals the effect of rumen-protected sulfur-containing amino acids on the meat quality of Tibetan sheep meat - Liu, JiQian; Han, Lijuan; Hou, Shengzhen; Gui, Linsheng; Yuan, Zhenzhen; Sun, Shengnan; Wang, Zhiyou; Yang, Baochun (Frontiers in Microbiology, 2024)
This study investigated the effects of rumen-protected sulfur-containing amino acids (RPSAA) on the rumen and jejunal microbiota as well as on the metabolites and meat quality of the longissimus lumborum (LL) in Tibetan sheep. By combining 16S rDNA sequencing with UHPLC-Q-TOF MS and Pearson correlation analysis, the relationship between gastrointestinal microbiota, muscle metabolites and meat quality was identified. The results showed that feeding RPSAA can increase the carcass weight, abdominal fat thickness (AP-2 group), and back fat thickness (AP-2 and AP-3 group) of Tibetan sheep. The water holding capacity (WHC), texture, and shear force (SF) of LL in the two groups also increased although the fatty acids content and brightness(L*) value significantly decreased in the AP-2 group. Metabolomics and correlation analysis further showed that RPSAA could significantly influence the metabolites in purine metabolism, thereby affecting L * and SF. In addition, RPSAA was beneficial for the fermentation of the rumen and jejunum. In both groups, the abundance of Prevotella 1, Lachnospiraceae NK3A20 group, Prevotella UCG-003, Lachnospiraceae ND3007 group in the rumen as well as the abundance of Eubacterium nodatum group and Mogibacterium group in the jejunum increased. In contrast, that of Turicibacter pathogens in the jejunum was reduced. The above microorganisms could regulate meat quality by regulating the metabolites (inosine, hypoxanthine, linoleic acid, palmitic acid, etc.) in purine and fatty acids metabolism. Overall, reducing the levels of crude proteins in the diet and feeding RPSAA is likely to improve the carcass quality of Tibetan sheep, with the addition of RPMET (AP-2) yielding the best edible quality, possibly due to its ability to influence the gastrointestinal microbiota to subsequently regulate muscle metabolites.